THE INFLUENCE OF LEADERSHIP STYLE ON PERFORMANCE EMPLOYEES MEDIATED BY WORK MOTIVATION AND WORKING CULTURE IN TRANSPORTATION SERVICE DEPARTMENT OF YOGYAKARTA - Wibisono, Kunto; Jayaningrum, Siti Kusandhitasari; Wijaya, Perta Surya Mega; Setyanta, Budi; Handayani, Krysty (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2024)
This study aims to determine the effect of (1) Leadership Style on Employee Performance, (2) Leadership Style on Work Motivation, (3) Work Motivation on Employee Performance, (4) Leadership Style on Employee Performance mediated by Work Motivation, (5) Style Leadership on Work Culture, (6) Work Culture on Employee Performance and (7) Leadership Style on Employee Performance mediated by Work Culture. Sampling uses Slovin Formula resulted in 84 respondents from a total of 107 employees of Transportation Service Department Yogyakarta. Methods of data collection uses questionnaires. This research uses Data Quality Test and Hierarchical Regression Analysis. The study results show that Leadership Style plays a positive role on Employee Performance. Leadership Style plays a positive role on Work Motivation. Work Motivation plays a positive role on Employee Performance and is expressed as a Mediator variable on the effect of Leadership Style on Employee Performance. Leadership style has no effect on employee performance. Work Culture is declared not a mediator on the influence of Leadership Style on Employee Performance.